2017
DOI: 10.1088/1361-6528/aa52ac
|View full text |Cite
|
Sign up to set email alerts
|

The prospects of phosphorene as an anode material for high-performance lithium-ion batteries: a fundamental study

Abstract: To completely understand lithium adsorption, diffusion, and capacity on the surface of phosphorene and, therefore, the prospects of phosphorene as an anode material for high-performance lithium-ion batteries (LIBs), we carried out density-functional-theory calculations and studied the lithium adsorption energy landscape, the lithium diffusion mobility, the lithium intercalation, and the lithium capacity of phosphorene. We also carried out, for the very first time, experimental measurement of the lithium capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 93 publications
1
39
0
Order By: Relevance
“…Data from refs. . The inset shows energy profiles of Li diffusion along the armchair and zigzag directions on phosphorene surface.…”
Section: Power and Energymentioning
confidence: 99%
See 2 more Smart Citations
“…Data from refs. . The inset shows energy profiles of Li diffusion along the armchair and zigzag directions on phosphorene surface.…”
Section: Power and Energymentioning
confidence: 99%
“…c) Charge–discharge voltage versus Li‐ion capacity curves tested at C/10 rate for phosphorene battery anodes. Reproduced with permission . Copyright 2017, IOP Publishing.…”
Section: Power and Energymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the ultrafast diffusion of Li ions along the zigzag directions of phosphorene due to the low shallow energy barrier (0.08 eV) is almost 10 4 and 10 2 times faster than that in graphene and MoS 2 , respectively, indicating that phosphorene possesses potentially excellent Li storage properties . Good reversibility has been also reported due to the self‐recovery of phosphorene monolayer when it is distorted during the intercalation of Li ions at high Li/P ratio . Therefore, favorable features of phosphorene as anodes of LIBs including ultrafast diffusivity, good reversibility, and high open circuit voltage have been demonstrated theoretically as a promising candidate as anodes toward high‐performance LIBs.…”
Section: Black Phosphorus For Lithium‐ion Batteriesmentioning
confidence: 99%
“…The puckered layer structure of BP provides 2D interstitial space for Li insertion and extraction. Owing to the unique properties of phosphorene, numbers of theoretical calculations have been carried out related to the diffusion of Li ions in phosphorene . It is found that stronger interaction between Li and phosphorene than that in graphene could potentially provide high open circuit voltage and enhance the electrochemical performance accordingly .…”
Section: Black Phosphorus For Lithium‐ion Batteriesmentioning
confidence: 99%